Isolated Radial Nerve Palsy in a Newborn Due to a Congenital Myofibroma: A Rare Case of Peripheral Nerve Injury - Serena Chiellino; Viola Fortini; Chiara Castellani; Pierluigi Vasarri (MDPI AG, 2024)
Isolated musculoskeletal infantile myofibroma is a rare tumor of pediatric age. The majority of cases are seen in children under two years old, but it can occur at any age as a painless enlarging mass that involves bone, skin, or soft tissue, typically accompanied by compression symptoms. Perineural involvement is extremely rare in myofibromas. Neurological impairment can occur during infancy but isolated nerve palsy, particularly in peripheral nerves within the upper extremity, is very uncommon. Neonatal radial nerve palsy is a rare entity caused by different conditions. Among these, we mention local tumors affecting peripheral nerves, such as myofibroma. There are few cases described in the literature, which mainly concern adult patients. The authors present a case of congenital isolated radial nerve palsy in a newborn with MF of the right elbow, which resulted in impairment of the wrist and finger extension. Following a six-month monitoring period, the patient underwent surgical treatment to restore function to his right wrist and hand. This involved excising the infiltrated radial nerve segment associated with palliative surgery. Despite the benignity of this lesion, severe nerve damage and perineural involvement may require surgical treatment with nerve resection and reconstruction.